Design of a composite wind turbine blade manufactured with the ONE SHOT BLADE® technology. (2021) - Damiano, Michele; Russo, Angela; Sellitto, Andrea; Vecchio, Enrico; Stellato, Tommaso; Riccio, Aniello
Abstract: In this work, the design steps of a 10-meter long fiberglass wind turbine blade are introduced. When designing the blade, the innovative manufacturing technology, named ONE SHOT BLADE® technology, able to produce wind turbine blades in "one-piece", has been taken into account. Critical deflection analyses, considering the most severe loading condition, such as the flapwise bending moment on pressure side, have been performed to verify that the structure complies with the international small wind turbine blade design regulations.